2018
DOI: 10.1101/mcs.a003384
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of genetic diagnosis illustrated by an atypical case of congenital hypoplastic anemia

Abstract: Diamond–Blackfan Anemia (DBA) is a rare polygenic disorder defined by congenital hypoplastic anemia with marked decrease or absence of bone marrow erythroid precursors. Identifying the specific genetic etiology is important for counseling and clinical management. A 6-yr-old boy with a clinical diagnosis of DBA has been followed by our pediatric hematology team since birth. His clinical course includes transfusion-dependent hypoplastic anemia and progressive autoimmune cytopenias. Genetic testing failed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Our second patient presented with persistent neutropenia and was known to have HL who have been treated using chemoradiotherapy and was under follow-up for the past 6 years. HL is a specific type of lymphoma with Sundin et al 16 1/1 1 immune thrombocytopenia Recurrent thrombocytopenia after treatment suggests a differential diagnosis rather than immune thrombocytopenia Fellmann et al 17 2/2 2 splenomegaly, 1 neutropenia Rule of WGS in immunodeficiency, and identifies IL17 receptor-A (IL17 RA) deficiency and DADA2 in siblings with inflammation and recurrent infection Cipe et al 18 1/1 1 sever neutropenia The first patient with severe neutropenia associated with DADA2 Hsu et al 19 1/1 1 neutropenia, anemia, GATA2 deficiency Total ADA2 loss, as in this case, may result in serious cytopenia rather than vasculopathy Claassen et al 20 1/1 1 hypoplastic anemia, 1 autoimmune cytopenia DADA2 as an appreciated etiology for hypoplastic anemia Ghurye et al 21 2/6 2 neutropenia, 1 lymphopenia, 2 bone marrow hypocellularity DADA2 consideration in unexplained cytopenia, especially with pan-hypogammaglobulinemia Rama et al 22 4/13 3 lymphopenias, 1 HSM Propose a DADA2 genetic diagnosis preliminary decision tree Alsultan et al 23 1/1 1 ALPS Successful treatment with anti-TNF Alabbas et al 3 2/2 2 Hodgkin lymphoma First reported ADA2 mutation in a patient with malignancy Hodgkin lymphoma Barzaghi et al 24 1/1 1 ALPS Successful treatment with HSCT Batu et al 25 2/6 distinct behavior and clinical characteristics. 31 In classical HL, diagnosis depends on the histologic demonstration of Reed-Sternberg cells that comprise 1% to 2% of the total tumor cell mass with a background of mixed inflammatory cells.…”
Section: Discussionmentioning
confidence: 86%
“…Our second patient presented with persistent neutropenia and was known to have HL who have been treated using chemoradiotherapy and was under follow-up for the past 6 years. HL is a specific type of lymphoma with Sundin et al 16 1/1 1 immune thrombocytopenia Recurrent thrombocytopenia after treatment suggests a differential diagnosis rather than immune thrombocytopenia Fellmann et al 17 2/2 2 splenomegaly, 1 neutropenia Rule of WGS in immunodeficiency, and identifies IL17 receptor-A (IL17 RA) deficiency and DADA2 in siblings with inflammation and recurrent infection Cipe et al 18 1/1 1 sever neutropenia The first patient with severe neutropenia associated with DADA2 Hsu et al 19 1/1 1 neutropenia, anemia, GATA2 deficiency Total ADA2 loss, as in this case, may result in serious cytopenia rather than vasculopathy Claassen et al 20 1/1 1 hypoplastic anemia, 1 autoimmune cytopenia DADA2 as an appreciated etiology for hypoplastic anemia Ghurye et al 21 2/6 2 neutropenia, 1 lymphopenia, 2 bone marrow hypocellularity DADA2 consideration in unexplained cytopenia, especially with pan-hypogammaglobulinemia Rama et al 22 4/13 3 lymphopenias, 1 HSM Propose a DADA2 genetic diagnosis preliminary decision tree Alsultan et al 23 1/1 1 ALPS Successful treatment with anti-TNF Alabbas et al 3 2/2 2 Hodgkin lymphoma First reported ADA2 mutation in a patient with malignancy Hodgkin lymphoma Barzaghi et al 24 1/1 1 ALPS Successful treatment with HSCT Batu et al 25 2/6 distinct behavior and clinical characteristics. 31 In classical HL, diagnosis depends on the histologic demonstration of Reed-Sternberg cells that comprise 1% to 2% of the total tumor cell mass with a background of mixed inflammatory cells.…”
Section: Discussionmentioning
confidence: 86%
“…Anaemia was reported in 97 patients (25.6%), of whom 4 showed a Blackfan-Diamond Anaemia and 23 Pure Red Aplasia [ 1 , 2 , 4 , 7 9 , 11 , 12 , 15 18 , 20 , 21 , 29 , 31 , 33 , 36 , 40 , 43 , 47 49 , 53 , 58 , 59 , 62 , 63 , 65 67 , 71 , 76 , 77 , 82 , 83 , 86 89 ]. Thrombocytopenia was described in 34 patients (8.9%) [ 1 , 4 , 8 , 9 , 11 , 12 , 15 , 17 , 18 , 21 , 36 , 40 , 42 , 49 , 60 , 65 , 67 , 83 ], neutropenia in 76 (20.1%) [ 1 , 4 , 8 , 9 , 11 , 12 , 15 , 17 , 18 , 21 , 22 , 32 , 36 , 38 , 42 , 43 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent infections were described in 70 patients (18.5%) in terms of recurrent cutaneous infections as abscesses, widespread warts or molluscum contagiosum, severe gastrointestinal infections, respiratory infections, otitis, or opportunistic infections [ 1 , 4 , 7 9 , 12 , 17 , 19 , 21 , 22 , 30 33 , 38 , 39 , 42 , 44 , 45 , 49 , 58 , 59 , 61 , 63 , 64 , 71 , 77 , 82 , 83 , 87 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their results also revealed the presence of rare mutations in other genes, such as CECR1 and GATA1 62 . Additionally, Claassen et al 66 illustrated the importance of considering non‐RP gene mutations, specifically CECR1 , in order to identify a small but important subset of patients representing an alternative aetiology of congenital hypoplastic anaemia, lacking the typical DBA mutations. Another study 67 demonstrated the diagnostic utility of WES with regard to prompt and effective diagnosis of DBA in mothers and children with a family history suspicious of germline mutations.…”
Section: Ngs Relevance In Disease Entities Of Hypoplastic Bone Marrowmentioning
confidence: 97%